Answer:
The solution of the given system is (x,y) = (1,4)
Step-by-step explanation:
Here, the given system of equation is:
x = -3 + y
26 x - 5 y = 6
Now, substitute x = -3 + y in the second equation , we get
26 x - 5 y = 6 ⇒ 26 (-3 + y) - 5 y = 6
or, 26(-3) + 26(y) - 5y = 6
⇒ - 78 + 26 y - 5y = 6
⇒ 21 y = 84
⇒ y = 84 / 21 = 4 or , y = 4
So x = -3 + y = -3 + 4 = 1
Hence, the solution of the given system is (x,y) = (1,4)
Step-by-step explanation:
5x-17 and 3x-11 are supplementary angles
They add up to 180 degrees
5x-17 + 3x - 11 = 180
8x - 28 = 180
8x= 208
x= 26
3x-11, 90, and 2y + 5 added together equal 180
3x-11 + 90 + 2y + 5 = 180
3(26) - 11 + 2y + 5 = 90
78 - 6 + 2y = 90
72 + 2y = 90
2y = 18
y = 9
I hope this helps!!!